Optimal trajectory tracking control for a wheeled mobile robot using backstepping technique - Said Fadlo; Abdelhafid Ait Elmahjoub; Nabila Rabbah (Institute of Advanced Engineering and Science, 2022)
This work studies an optimal trajectory tracking of a wheeled mobile robot with the objective of minimizing energy consumption. First, the mathematical model, which takes into account the kinematic model of the mobile robot and the dynamic model of the actuators is presented. Then, a backstepping controller is designed and its parameters are tuned to satisfy several strict criteria such as rapid convergence, matching desired trajectory, and minimizing energy. For that, two cost functions were investigated and the best one has been selected. The significant reduction in energy losses achieved for all the proposed motion scenarios proves the effectiveness of our approach.